PTPN11 Mutations in the Ras-MAPK Signaling Pathway Affect Human White Matter Microstructure. (29th October 2020) - Fattah, Mustafa; Raman, Mira M; Reiss, Allan L; Green, Tamar
Abstract: We examined whether PTPN11 mutations affect the white matter connectivity of the developing human brain. Germline activating mutations to the PTPN11 gene cause overactivation of the Ras-Mitogen-Activated Protein Kinase pathway. Activating mutations cause Noonan syndrome (NS), a developmental disorder associated with hyperactivity and cognitive weakness in attention, executive function, and memory. In mouse models of NS, PTPN11 mutations cause reduced axon myelination and white matter formation, while the effects of PTPN11 mutations on human white matter are largely unknown. For the first time, we assessed 17 children with NS (9 females, mean age, 8.68 ± 2.39) and 17 age- and sex-matched controls (9 female, mean age, 8.71 ± 2.40) using diffusion brain imaging for white matter connectivity and structural magnetic resonance imaging to characterize brain morphology. Children with NS showed widespread reductions in fractional anisotropy (FA; 82 613 voxels, t = 1.49, P < 0.05) and increases in radial diffusivity (RD; 94 044 voxels, t = 1.22, P < 0.05), denoting decreased white matter connectivity. In NS, the FA of the posterior thalamic radiation correlated positively with inhibition performance, whereas connectivity in the genu of the corpus callosum was inversely associated with auditory attention performance. Additionally, we observed negative and positive correlations, respectively, between memory and the cingulum hippocampus, and memory and the cingulum cingulate gyrus. These findings elucidate the neural mechanism underpinning the NS cognitive phenotype, and may serve as a brain-based biomarker.